Estimating the Gini index for heavy-tailed income distributions - Bari, Amina; Rassoul, Abdelaziz; Rouis, Hamid Ould (South African Statistical Journal, 2021)
In the present paper, we define and study one of the most popular indices which measures the inequality of capital incomes, known as the Gini index. We construct a semiparametric estimator for the Gini index in case of heavy-tailed income distributions and we establish its asymptotic distribution and derive bounds of confidence. We explore the performance of the confidence bounds in a simulation study and draw conclusions about capital incomes in some income distributions.